Evaluation of genomic DNA extraction methods for the identification of Leptospira spp. in bovine urine samples by PCR - Revelo Ruales, Alexandra Paola (2020)
The purpose of this study was to select for the extraction of DNA from Leptospira spp from urine samples for the diagnosis of bovine leptospirosis by PCR. Three methods of DNA extraction methods were used: Ethanol-Sodium Hydroxide (EtNa), Chelex® 100 chelating resin and the PureLink® Genomic DNA Mini Kit commercial extraction case. The extracted DNA served for the standardization of three PCR protocols for the identification of the rrl, hap1 and rrs genes, respectively, in the AGROCALIDAD, Ecuador laboratory. A total of 72 bovine urine samples were collected from livestock farms in the province of Manabí, Ecuador. Ten positive samples were obtained by amplifying the rrl gene, which identifies the genus Leptospira. Of the genus-positive samples, eight amplified for the hap1 gene, which codes for the main outer membrane protein of pathogenic species. The agreement between the DNA extraction methods was evaluated with Chelex-100, and the PureLink® Genomic DNA Mini Kit, determining a agreement of 0.74 using the Kappa index.